2022
DOI: 10.3390/ma15103566
|View full text |Cite
|
Sign up to set email alerts
|

Contribution Ratio Assessment of Process Parameters on Robotic Milling Performance

Abstract: Robotic milling has broad application prospects in many processing fields. However, the milling performance of a robot in a certain posture, such as in face milling or grooving tasks, is extremely sensitive to process parameters due to the influence of the serial structure of the robot system. Improper process parameters are prone to produce machining defects such as low surface quality. These deficiencies substantially decrease the further application development of robotic milling. Therefore, this paper sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The milling process parameters can also be specifically defined for a robotic arm implementation. In [ 48 ], the authors found that spindle speed dictates the surface roughness, while milling depth dictates the vibration. The problem of milling parts with low rigidity is a common topic in the aircraft industry, requiring vibration-controlled approaches [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The milling process parameters can also be specifically defined for a robotic arm implementation. In [ 48 ], the authors found that spindle speed dictates the surface roughness, while milling depth dictates the vibration. The problem of milling parts with low rigidity is a common topic in the aircraft industry, requiring vibration-controlled approaches [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a comprehensive understanding of the impact of machining parameters on dynamic errors in HMC is crucial for achieving high-quality robotic machining in HMC. Current research on robotic machining primarily focuses on investigating the impact of machining parameters on machining quality [25,35], vibration analysis in relation to machining parameters [11], prediction of machining quality based on parameters and vibrations [12], and more [38]. However, there is still a need for further understanding of the relationship between machining parameters and dynamic errors in robotic machining.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of reasonable milling parameters plays an important role in the effective avoidance of chatter for six-DOF robots. Studies have shown that milling parameters such as spindle speed, radial depth of cut, and axial depth of cut have certain effects on chatter stability [17][18][19] . But the effect of feed rate is generally ignored.…”
Section: Introductionmentioning
confidence: 99%